The Lively Practice of Dérsanä Rufaýel (Homily of Raphael) in Ethiopian Healing Tradition - Woldehana, Wondwosen Admasu; Assefa, Abba Daniel (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This article focuses on the living practice of Dérsanä Rufaýel in the Ethiopian healing tradition. Homily of Raphael is one of the earliest religious books in the EOTC tradition. The study examines use of Dérsanä Rufaýel in the healing tradition of Ethiopia in liturgical and spiritual practice. Major aim of the study is to identify the applicability of manuscripts of Raphael's homilies in alleviating ailments and other problems and to examine their significance in the Ethiopian tradition. It will be studied based on a critical edition prepared by the author from the main part of his doctoral dissertation. The content analysis of the critical edition of Dérsanä Rufaýel will, together with inter-textually related texts, show its significant impact on the Ethiopian tradition. The study also includes indirect observation of healing services in some of St. Raphael's churches in some parts of Ethiopia. The research shows that the Homily of Raphael is one of the available liturgical books on the motif of healing in the Ethiopian Orthodox Täwahédo Church as well as illustrated in Mäséhäfä Sénksar and in the annual and monthly celebrations. Healing is thus particularly associated with the devotion to the glorious archangel Rufaýel, whereby the faithful followers of the EOTC celebrate this day and use the holy water to cure themselves from their ailments and other problems.